PENGEMBANGAN MINAT WIRAUSAHA SISWA DI SEKOLAH MENENGAH KEJURUAN NEGERI (SMKN) 4 KOTA SERANG - Bukhari, Ahmad; Saleh, Khaerul (CV. Era Digital Nusantara, 2024)
Entrepreneurship is a mindset that encourages individuals to create a business. Intention is a certain desire that a person has to do something or act and be able to develop new products or ideas and be able to build a business with new concepts. Entrepreneurs are required to be creative and have the ability to see business opportunities. For teenagers who want to start entrepreneurship, start early so that later they can become successful entrepreneurs, education and training are the only capital to become an entrepreneur. But the real learning and struggle will begin when you try it. In entrepreneurship, of course you must have basic entrepreneurship education to be able to help individuals develop entrepreneurial desires, spirit and behavior. Education can be a source of attitude and overall intention to become a successful entrepreneur in the future.